Analysis of production system in the food plan section at PT. Benih Citra Asia Indonesia - Mahendra, Muhammad Hadyanshah; Mas’ud, Ahmad Ibnu; Siswanto, Adil (YAYASAN MITRA PERSADA NUSANTARA, 2025)
This research focuses on analyzing the production system in the Food Plan section at PT. Benih Citra Asia-Indonesia. A company engaged in the production of superior seeds for food crops and horticulture. This research aims to understand the seed production process, identify constraints in production, andprovide recommendations for improvement. The research methodology used is a descriptive approach with direct observation, interviews, and analysis of secondary data from the company. The research sampleinvolved employees in the production division and related sections at PT. Benih Citra Asia. The results showed that the seed production process at PT. Benih Citra Asia includes several main stages, namely (1)seed incoming,; (2) seed processing; (3) seed storage; (4) seed packing, and (4) product storage. The main obstacles found are the mixture of other varieties in : (1) seed sorting; (2) barcode mismatches with harvestreceipts, and (3) negligence in seed sorting. The proposed solutions include; (1) increased monitoring of seed quality; (2) improved barcode recording system; and (3) training for employees to improve accuracy inthe sorting process. Overall, this study shows that PT. Benih Citra Asia has implemented a good production system, but there are still some aspects that need to be improved to increase efficiency and productquality. This research is expected to provide insights for the seed industry and become a reference for companies in improving the quality of seed production.